2005
DOI: 10.1002/pmic.200401294
|View full text |Cite
|
Sign up to set email alerts
|

Printing of protein microarrays via a capillary-free fluid jetting mechanism

Abstract: Current proteomics experiments rely upon printing techniques such as ink jet, pin, or quill arrayers that were developed for the creation of cDNA microarrays. These techniques often do not meet the requirements needed for successful spotting of proteins to perform high-throughput, array-based proteomic profiling. Biological laser printing (BioLP) is a spotting technology that does not rely on solid pins, quill pins, or capillary-based fluidics. The non-contact mechanism of BioLP utilizes a focused laser pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 26 publications
(17 reference statements)
0
65
2
1
Order By: Relevance
“…21,22 Images of the LIFT process in the case of a barium-zirconium titanate/terpineol ͑BaTiO 3 ͒ suspension, 21 a viscous paste with a rheology clearly different from that of the present experiment, showed the development of a turbulent and irregular jet which fragmented into multiple droplets short after its formation. On the other hand, and also under different conditions from those of the present experiment, images of the process using a bovine serum albumin solution 22 showed the formation of a thin and blurred jet which broke into multiple droplets after traveling only 200 m. Moreover, it also has to be noted that in the present experiment a direct correlation between the deposits and time-resolved images can be established. In fact, it has been found that for the range of laser fluences leading to the deposition of circular droplets liquid transfer is mediated by the formation of very long and stable jets, and therefore droplet deposition must be due to the contact of the long and stable jet with the receptor substrate, as we had previously pointed out.…”
Section: B Time-resolved Imagingcontrasting
confidence: 53%
See 1 more Smart Citation
“…21,22 Images of the LIFT process in the case of a barium-zirconium titanate/terpineol ͑BaTiO 3 ͒ suspension, 21 a viscous paste with a rheology clearly different from that of the present experiment, showed the development of a turbulent and irregular jet which fragmented into multiple droplets short after its formation. On the other hand, and also under different conditions from those of the present experiment, images of the process using a bovine serum albumin solution 22 showed the formation of a thin and blurred jet which broke into multiple droplets after traveling only 200 m. Moreover, it also has to be noted that in the present experiment a direct correlation between the deposits and time-resolved images can be established. In fact, it has been found that for the range of laser fluences leading to the deposition of circular droplets liquid transfer is mediated by the formation of very long and stable jets, and therefore droplet deposition must be due to the contact of the long and stable jet with the receptor substrate, as we had previously pointed out.…”
Section: B Time-resolved Imagingcontrasting
confidence: 53%
“…21 In that work, a study of the process dynamics at different laser fluences was reported; however, for such a suspension and irradiation conditions, material deposition did not take place in the form of a single droplet on the receptor, but rather as a set of multiple droplets. The time-resolved images of the LIFT process for a biomolecule containing solution 22 did not either provide the information necessary to unveil the transfer mechanism. In that case, a direct correlation between time-resolved images and deposited material could not be carried out, since the conditions at which images were acquired differed from those of the deposits.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to conventional printing techniques, laser-induced forward transfer (LIFT) has been demonstrated to be feasible for printing biomolecules [7][8][9][10][11][12][13], biomolecule structures [14], as well as cells [15], and micro-organisms [16,17]. In LIFT, a laser beam is focused or imaged through a transparent support onto the backside of a metallic or polymer thin film [11,14,16] coated with the material to be transferred.…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of cell printers described in the literature ranging from jet-based to extrusion-based techniques . In general, jet-based techniques are more precise than extrusion-based methods, and typically deposit lowvolume droplets (0.5-1000 pL) in rapid succession (100-10,000/s) (Barron et al, 2005a;Ringeisen et al, 2002;Roth et al, 2004;Xu et al, 2006). Due to the low volume of each printed droplet, biological laser printing, or BioLP, is able to pattern single cells onto different surfaces with micron-scale resolution (Barron et al, 2005b;Othon et al, 2008;Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The light energy from the laser pulse was converted into heat energy at the quartz/TiO 2 layer, and the heat vaporized a portion of the virus culture medium (bioink) in direct contact with the metal oxide layer (Barron et al, 2004b). High speed images of this energy transfer process have show that a liquid jet is forced away from the quartz slide (Barron et al, 2005a). The quartz slide and receiving substrate were computer controlled and could be moved independently, such that with successive laser pulses, patterns could be directly written drop-by-drop onto the receiving substrate.…”
Section: Introductionmentioning
confidence: 99%